1996
DOI: 10.1093/jat/20.6.432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 3,4-Methylenedioxymethamphetamine (MDMA) and its Metabolites in Plasma and Urine by HPLC-DAD and GC-MS

Abstract: In Europe, the compound 3,4-methylenedioxymethamphetamine (MDMA, Ecstasy, Adam), in addition to cannabis, is the most abused illicit drug at all-night "techno" parties. Methods for the determination of MDMA and its metabolites, 4-hydroxy-3-methoxymethamphetamine (HMMA), 3,4-dihydroxy-methamphetamine (HHMA), 3,4-methylenedioxyamphetamine (MDA), 4-hydroxy-3-methoxyamphetamine (HMA), and 3,4-dihydroxyamphetamine (HHA), in biological fluids were established. Plasma and urine samples were collected from two patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 45 publications
6
81
0
5
Order By: Relevance
“…Citalopram could have prolonged the presence of MDMA in the blood, thereby delaying subjective effects. This argument is weakened, however, by the report that doses of 1.5 mg/kg MDMA produced peak blood levels of 330 ng/ml after 120 min and levels of 150 ng/ml lasting over nine hours (Helmlin et al 1996). Thus, effective plasma levels of MDMA appear to outlast its psychological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Citalopram could have prolonged the presence of MDMA in the blood, thereby delaying subjective effects. This argument is weakened, however, by the report that doses of 1.5 mg/kg MDMA produced peak blood levels of 330 ng/ml after 120 min and levels of 150 ng/ml lasting over nine hours (Helmlin et al 1996). Thus, effective plasma levels of MDMA appear to outlast its psychological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, sustained concentrations of MDMA (or MDA) hours after administration, rather than initial high peak MDMA levels, such as those seen after subcutaneous administration (Figure 1), may be more closely related to the neurotoxic process. Regardless of which pharmacokinetic parameter is most closely linked to MDMA's long-term effects, the pharmacokinetic profile differences presently observed suggest that, if a goal is to elucidate possible long-term effects of MDMA in humans, the oral route of administration may be preferable in preclinical studies, because it avoids the higher initial MDMA C max , as well as the greater AUC, observed after subcutaneous administration, and because it engenders a pharmacokinetic profile that more closely resembles that seen in humans (Helmlin et al, 1996;de la Torre et al, 2000de la Torre et al, , 2004Pacifici et al, 2002). Although in our initial route of administration/pharmacokinetic study we cannot definitively exclude an order effect (because the subcutaneous route was tested before the oral route), we do not believe it accounts for the observed differences because, on average, 8 weeks had elapsed between subcutaneous and oral MDMA testing (Table 1).…”
Section: Route Of Administrationmentioning
confidence: 99%
“…Studies in Switzerland have investigated MDMA's action on brain neurotransmitter receptor sites (Liechti et al 2000), on information processing (Vollenweider et al 1999b) and on the psychological and cardiovascular effects of a single dose of MDMA (Vollenweider 1998). Three MDMA pharmacokinetic studies have been conducted in Europe in England (Fallon et al 1999), Spain (de la , and Switzerland (Helmlin et al 1996). A Phase I dose-response safety study has been completed place in Spain (Mas et al 1999;Cami et al 2000), as well as a study investigating MDMA/alcohol interactions (Hernandez-Lopez et al 2002).…”
Section: Why Mdma?mentioning
confidence: 99%